Diffuse pigmented villonodular synovitis in knee joint: diagnosis and treatment - Eduardo Frois Temponi; Antônio Augusto Guimarães Barros; Vinícius Oliveira Paganini; Victor Atsushi Kasuya Barbosa; Roger Badet; Lúcio Honório de Carvalho Júnior (Revista Brasileira de Ortopedia)
ABSTRACT Pigmented villonodular synovitis is a rare proliferative condition of the synovium. Although the condition can present in any joint, the knee is the most commonly affected site. Despite being a benign condition, pigmented villonodular synovitis is often aggressive, with marked extra-articular extension in some cases. Monoarticular involvement occurs in two forms: localized and diffuse. The latter is more common, with a high recurrence rate. There is no standard method of management of this lesion. Open surgery is a classical and effective method for treatment. Arthroscopic synovectomy, however, has gained popularity, and has several advantages over the open technique particularly in exclusively articular cases. The combined approach is suggested in cases with extra-articular involvement. Synovectomy through any approach may prevent secondary osteoarthritis and subsequent joint arthroplasty. Internal irradiation or external beam radiation as an adjuvant treatment to surgical synovectomy appears to decrease the rate of local recurrence in diffuse cases. The authors observed a great heterogeneity in reporting of functional results, and specific conclusions should not be drawn. Each patient should be managed in accordance with his/her particular condition.